Diagnosis and recommendation integrated system (DRIS) model establishment for diagnosing Sorghum (Sorghum bicolor) nutrient status in Benin (West Africa) - DAGBENONBAKIN, Gustave D.; Kindomihou, Valentin Missiakô; Agbangba, Emile C.; Sokpon, Nestor; SINSIN, Brice (My University, 2013)
The Diagnosis and Recommendation Integrated System (DRIS) is a potential method for interpreting plant foliar nutrient composition. It provides a reliable means of linking leaf nutrient concentrations to the yield of sorghum, and has been developed for this crop using experimental data from organic and inorganic trials carried out in the Upper Catchment of Benin. Grain yield and leaf nutrient concentration were used to establish DRIS norms for N, P, K, Mg, Ca, S and Zn and statistical parameters for sorghum. The DRIS norms provided by this study were N/P: 6.5, K/N: 0.7, N/Ca: 4.6, S/N: 0.1, N/Zn: 712.2, K/P: 4.7, P/Ca: 0.7, S/P: 0.4, Zn/P: 0.01, K/Ca: 3.3, S/K: 0.1, K/Zn: 510.1, S/Zn: 39.0, Ca/Zn: 164.0, and S/Ca: 0.3. Although the database was relatively small, the norms derived for nutrient ratios of key biological significance, that is, N/S and K/N, were within the expected narrow ranges for higher plants, giving credibility to both the database and the DRIS model. Data from future surveys and field experiments may subsequently be used to enlarge the database allowing the refinement of model parameters and hopefully an expansion of the diagnostic scope such as to include other micro- nutrients. As it stands, this preliminary DRIS model for sorghum offers a good diagnostic tool for evaluating the N, P, K, Ca, S and Zn status of sorghum crops in Benin.
Keywords: DRIS norms; grain yield; sorghum; Benin.